2020
DOI: 10.1177/2045125320950124
|View full text |Cite
|
Sign up to set email alerts
|

A survey of UK general practitioners about depression, antidepressants and withdrawal: implementing the 2019 Public Health England report

Abstract: Background: In 2019, a literature review indicated that more than half of people who try to come off antidepressants experience withdrawal effects. Both the National Institute of Health and Care Excellence and the Royal College of Psychiatrists updated their positions in line with that review, and Public Health England published a 152-page report called Dependence and withdrawal associated with some prescribed medicines: an evidence review. The report made several recommendations relevant to general practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…50 A lack of sufficient information on discontinuation was also identified as a key issue for GPs. 27,49 The same concerns were reported by GPs in Holland. 28,51…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…50 A lack of sufficient information on discontinuation was also identified as a key issue for GPs. 27,49 The same concerns were reported by GPs in Holland. 28,51…”
Section: Discussionsupporting
confidence: 64%
“…Patients reported that GPs recommended tapers that were too quick, causing intolerable withdrawal symptoms. Previous research has identified that GPs do not feel confident in their knowledge of helping patients to come off antidepressants 49 ; in particular, they described being dissatisfied with current NICE guidance, indicating that ‘it is unclear (especially regarding tapering regimes), limited, not accessible and at times not applicable to real patients’, 50 with one GP describing the current NICE guidance on discontinuing antidepressants ‘as a bit pants’. 50 A lack of sufficient information on discontinuation was also identified as a key issue for GPs.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging that a recent survey of UK general practitioners (GPs) (albeit with a curtailed sample size due to Covid-19) just reported that although there was ‘a marked lack of consistency in GPs’ knowledge about the incidence and duration of withdrawal effects’ two-thirds said they would welcome more training on these matters. 59 …”
Section: Discussionmentioning
confidence: 99%
“…A recent survey conducted in the United Kingdom found that the number of individuals living with depression had almost doubled during the pandemic [ 5 ]. Given the significant rise in the prevalence of depression associated with COVID-19, the consumption of antidepressants (ADs) had also increased worldwide [ 4 , 6 ]. The sharp rise in the consumption of ADs is a major concern given the limited evidence on long-term effectiveness and safety of ADs.…”
Section: Introductionmentioning
confidence: 99%